Ferry Transport Service Quality Gap Analysis: Evidence Of South Sumatera Areas - Rhaptyalyani Herno Della; Debby Yulinar Permata; Ashari Fitra Rachmannullah; Edi Kadarsa (Politeknik Transportasi Darat Indonesia - STTD Bekasi, 2025)
Transportation service quality is essential to ensure optimal performance of infrastructure, facilities, and the benefits delivered to users. Service quality can be evaluated by comparing passenger expectations with the company’s perception, allowing identification of gaps in service delivery. This study conducts a gap analysis by distributing questionnaires to both ferry passengers and service employees to examine differences in their perceptions of service quality. The assessment adopts the SERVQUAL framework, encompassing tangible, reliability, responsiveness, assurance, and empathy dimensions. Furthermore, the PZB model and paired t-test method are applied to evaluate discrepancies between expected and perceived services from the passengers’ perspective, as well as to assess service provision, service design standards, company perceptions, and external communication. The analysis focuses on ferry routes in South Sumatra, specifically the Tanjung Api-Api and Tanjung Kalian corridors, where the results indicate that the most significant gap occurs in the tangible dimension. These findings highlight the need for ferry operators to improve service quality, particularly in areas with the largest gaps. This study also provides practical implications for further evaluation and optimization of ferry services, supporting their role as a key mode of transportation in maritime countries such as Indonesia.